Modelagem da propagação acústica em águas rasas em apoio à implantação de redes de comunicação acústica submarina - Simões, Marcus Vinícius da Silva. (2018)
Since the 1980s, digital communication has been one of the major topics in underwater acoustics research. Furthermore, underwater waveguide modeling development has been also improved not only taking advantage of computational power available but also due to increasing data variety and volume provided by the new generation of data acquisition oceanographic instruments. According to Jensen, Kuperman, Porter, e Schmidt [1] normal mode acoustic propagation models are more accurate for frequencies below 1 kHz and propagations in range independent environments, with ray theory being applied for frequency values above 1 kHz and range dependent environments. The proposed model uses the adiabatic coupling properties of the modes, extending the classic two-layer waveguide model of Pekeris [2] to a three layers model with a different approach for surface and bottom interacting modes, considering an adiabatic and time invariant channel. In order to validate the model, the synthetic results computed on the measurement of transmission loss between two nodes were compared with measurements in situ obtained in a field experiment. The results are presented for four different paths among nodes of the proposed network with all of them under full upwelling condition on the experiment site. The synthetic results were qualitatively good but with absolute values for transmission loss requiring improvements on the convergence of synthetic and real in situ measurements.